TITLE - Nisha K. M; Mohd Asif Khan (Journal of Entrepreneurship, Management and Innovation)

(untitled)
The new millennium is seen as an epoch of entrepreneurship with entrepreneurs perceiving novel opportunities, organizing resources, undertaking risks to pursue their goals in establishing innovative ventures for scaling new horizons. Women entrepreneurs have the potency to confront numerous challenges, such as creating equity, equilibrium, ensuring sustainable and inclusive socio economic development in divergent economies, by seizing tremendous business opportunities in the contemporary commercial world. Kerala, the southern State of India, is experiencing an economic renovation through technological transformation and, in particular, through the growth of women oriented Micro, Small and Medium Enterprises (MSMEs). The study aims to; identify the growth trends of women’s entrepreneurship in the micro enterprises of Kerala; examine whether women’s entrepreneurial activities significantly vary across the form of women owned enterprises, type of organization and nature of activity; and also explore the prospects and challenges faced by women entrepreneurs through micro entrepreneurial activities. Research methodology involves the application of descriptive quantitative analysis on the secondary data primarily collected from the database of Directorate of Industries and District Industries Centre for a period of 7 years extending from 2007-08 to 2013-14. Findings reveal that MSMEs spawn better income distribution, by operating in heterogeneous areas of the economy with limited capital and creating more employment opportunities, thereby reducing poverty and inequalities. The trend analysis reflects an escalation in the number of enterprises, investments, profits and employment opportunities generated especially through micro enterprises of women. They play a crucial role in the economy in terms of creating self employment and generating employment opportunities for others. A paradigm shift is seen in the role of women’s entrepreneurship in terms of innovation, attitudes, leadership qualities, competitiveness, entrepreneurial skill and absorbing new entrants to the job market, empowering marginalized women.